If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 36 = 39 Reorder the terms: 36 + 2x = 39 Solving 36 + 2x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 2x = 39 + -36 Combine like terms: 36 + -36 = 0 0 + 2x = 39 + -36 2x = 39 + -36 Combine like terms: 39 + -36 = 3 2x = 3 Divide each side by '2'. x = 1.5 Simplifying x = 1.5
| 3.5x-1=1.2(-7x+2) | | -5+7(2x-6)= | | -4x+2(5x-6)=-3x-39 | | 4x+11=27 | | 2(3-5x)+3= | | 2x+5(0)=10 | | -10p-2+9p=3p+6 | | 2(3-5)+3= | | g(2x)=2x-6 | | 2x+5(y)=10 | | 5x+65=10x-5 | | -10x+3(8+x)=-6(x-4) | | 4-2(3x+6)= | | 5x+y=-4 | | 10x+3(8+x)=-6(x-4) | | 2(x)+20=10 | | 3x(2x+5)=0 | | -8n-5(3n-5)= | | 2-3(3+7v)= | | 20+5(y)=10 | | 6(6x+6)-5=1+6x | | -5(v-7)-2= | | 3(7x-8)-8= | | 62-2x=7x+21 | | (-3t)=-9 | | 4lb+1.20=7.20 | | 5-10x=113-31x | | -7(-8k+6)+6k= | | 8(2x-3)=6x-9 | | 2+14z=-8+9 | | 3b-5(b+1)=0 | | 4x+13=-113-10x |